A survey of mobility management in next-generation all-IP-based wireless systems. - Akyildiz, I.F (IEEE Wireless communications)
Next-generation wireless systems are envisioned to have an IP-based infrastructure with the support of heterogeneous access technologies. One of the research challenges for next generation all-IP-based wireless systems is the design of intelligent mobility management techniques that take advantage of IP-based technologies to achieve global roaming among various access technologies. Next-generation wireless systems call for the integration and interoperation of mobility management techniques in heterogeneous networks. In this article the current state of the art for mobility management in next-generation all-IP-based wireless systems is presented. The previously proposed solutions based on different layers are reviewed, and their qualitative comparisons are given. A new wireless network architecture for mobility management is introduced, and related open research issues are discussed in detail.